PENGARUH INFLASI, PDRB, DAN UPAH MINIMUM TERHADAP PENYERAPAN TENAGA KERJA DI PROVINSI JAWA TIMUR - Ghaly Muhammad Danianto (Politeknik Bisnis Indonesia, 2023)
The purpose of the study is to ascertain if East Java's labour absorption is impacted by inflation, the gross regional product, and the minimum wage. This study employs a quantitative research technique, with three independent variables inflation, gross regional domestic product (GRDP), and minimum wage and one dependent variable, labour. The time series of yearly data used in this study spans the years 2006 through 2021. Secondary data from the East Java Province and the Indonesian Central Bureau of Statistics (BPS) were used in this study. Following data collection for this project, multiple linear regression analysis was used to examine the data. From the results of the data processing above, it can be seen that the independent variable Provincial Minimum Wage (UMP) has no significant effect on the labour absorption variable in East Java Province, while the independent variable Gross Regional Domestic Product (GDP) has a significant positive effect on the employment absorption variable in East Java Province.